Negotiating the riskscapes of convenience food - Everts, Jonathan; Jackson, Peter; Meah, Angela; Viehoff, Valerie (ERDKUNDE, 2018)
Addressing the spatial dimensions of risk, this paper examines the multiple ways that consumers negotiate the ‘riskscapes’ associated with the consumption of convenience food. It explores how convenience food poses a range of risks and potential ways of mitigating those risks. Drawing on empirical research from Germany and the UK, the paper demonstrates how food risks should be contextualized within the practices of everyday life and how consumer understandings of risk differ from expert risk assessments. The paper locates a number of different sites within the riskscape associated with convenience food, going beyond the focus on food safety and security that are the main concerns of health authorities and government advisors. Deficit models of food risk are criticised and alternatives are proposed that emphasise the socially embedded nature of risk within the practices of everyday life.